Epigenetics: the language of the cell?. (February 2014) - Huang, Biao; Jiang, Cizhong; Zhang, Rongxin
Epigenetics is one of the most rapidly developing fields of biological research. Breakthroughs in several technologies have enabled the possibility of genome-wide epigenetic research, for example the mapping of human genome-wide DNA methylation. In addition, with the development of various high-throughput and high-resolution sequencing technologies, a large number of functional noncoding RNAs have been identified. Massive studies indicated that these functional ncRNA also play an important role in epigenetics. In this review, we gain inspiration from the recent proposal of the ceRNAs hypothesis. This hypothesis proposes that miRNAs act as a language of communication. Accordingly, we further deduce that all of epigenetics may functionally acquire such a unique language characteristic. In summary, various epigenetic markers may not only participate in regulating cellular processes, but they may also act as the intracellular 'language' of communication and are involved in extensive information exchanges within cell.